SHARE VALUE DIFFERENCES PT. KIMIA FARMA TBK TOWARDS THE ACQUISITION OF SHARE EVENTS IN PT. PHAPROS TBK - Revi Candra; Elmiliyani Wahyuni-S; Nailatul Hanifah (UNIB Press, 2021)
TThis study aims to determine whether there is a difference in the value of the shares of PT. Kimia Farma Tbk. after the acquisition of PT. Phapros Tbk. The data used is the value of shares consisting of book value, market value, and the intrinsic value of shares of PT. Kimia Farma Tbk, which was taken ten months before the acquisition of PT. Phapros Tbk. by PT Kimia Farma Tbk. This study is a comparative study with a quantitative descriptive approach, data analysis using the Wilcoxon signed-rank test. The results of this study indicate that the book value of PT. Kimia Farma Tbk. which has a significant difference before and after the acquisition, while the indicators of the stock market value and the intrinsic value of PT. Kimia Farma Tbk. does not have a significant difference before and after the acquisition event.